Analisis Flash Sale Promotion, Online Customer Review, dan Celebrity Endorser Terhadap Purchase Interest pada E-Commerce: Studi pada Aplikasi Shopee - Eka Oktaviani; Satrio Sudarso; Misti Hariasih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was carried out to analyze how much influence the Flash Sale Promotion, Online Customer Review, and Celebrity Endorser variables have on Purchase Interest in E-Commerce, namely the Shopee application. The method used is a quantitative method, and the technique used for research is nonprobability sampling using a purposive sampling technique and the number of respondents is 100 people. The test model used by researchers in processing research data is the multiple regression analysis test, including Validity Test and Reliability Test, Normality Test, Multicollinearity Test, Autocorrelation Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Partial Significance Test (T Test), Simultaneous Significance Test (F Test), Coefficient of Determination Test (R2). And the data was processed using the IBM SPSS version 29 application. The results of this research show that the flash sale promotion variable partially has no effect on buying interest, while the online customer review and celebrity endorser variables partially have a positive and significant influence on buying interest. Simultaneously, the flash sale promotion, online customer review, and celebrity endorser variables have an influence on the purchase interest variable.